Anomalously high arsenic concentration in a West Antarctic ice core and its relationship to copper mining in Chile. (January 2016) - Schwanck, Franciele; Simões, Jefferson C.; Handley, Michael; Mayewski, Paul A.; Bernardo, Ronaldo T.; Aquino, Francisco E.
Abstract: Arsenic variability records are preserved in snow and ice cores and can be utilized to reconstruct air pollution history. The Mount Johns ice core (79°55′S; 94°23′W and 91.2 m depth) was collected from the West Antarctic Ice Sheet in the 2008/09 austral summer. Here, we report the As concentration variability as determined by 2137 samples from the upper 45 m of this core using ICP-SFMS (CCI, University of Maine, USA). The record covers approximately 125 years (1883–2008) showing a mean concentration of 4.32 pg g −1 . The arsenic concentration in the core follows global copper mining evolution, particularly in Chile (the largest producer of Cu). From 1940 to 1990, copper-mining production increased along with arsenic concentrations in the MJ core, from 1.92 pg g −1 (before 1900) to 7.94 pg g −1 (1950). In the last two decades, environmental regulations for As emissions have been implemented, forcing smelters to treat their gases to conform to national and international environmental standards. In Chile, decontamination plants required by the government started operating from 1993 to 2000. Thereafter, Chilean copper production more than doubled while As emission levels declined, and the same reduction was observed in the Mount Johns ice core. After 1999, arsenic concentrations in our samples decreased to levels comparable to the period before 1900.